Pengaruh Environmental, Social, and Governance (ESG) terhadap Kinerja Perusahaan pada Perusahaan Pertambangan yang Terdaftar dalam JII 70 - Rahmah Fitri Emiati; Ady Cahyadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) on the financial performance of mining companies listed in the Jakarta Islamic Index (JII70) for the 2020–2024 period, with the Debt to Equity Ratio (DER) as a control variable. The findings show that, partially, the Environmental variable has a positive but insignificant effect on ROA, indicating that efforts in energy efficiency, waste management, and emission reduction have not yet been fully reflected in short-term profitability. In contrast, the Social variable has a significant effect on ROA, emphasizing that companies’ engagement in building stakeholder relationships, protecting employee rights, and implementing social responsibility programs contribute substantially to financial performance. The Governance variable also has a significant effect on ROA, highlighting the importance of good governance practices, transparency, and accountability in enhancing profitability. Meanwhile, the control variable DER shows no significant effect on ROA. Simultaneously, ESG performance has a significant effect on ROA, proving that integrated ESG implementation supports the profitability of mining companies. These findings confirm that ESG is not only a compliance measure with sustainability principles but also a long-term business strategy that strengthens companies’ competitiveness and serves as a crucial consideration for investors in making investment decisions.